Pengembangan Sistem Rekomendasi Melalui Pendekatan Web Semantik dan Simple Additive Weighting (SAW) - Pramartha, Cokorda; Jayadi, I Putu Indie Surya; Atmaja, I Dewa Made Bayu (Prahasta Publisher, 2022)
Indonesia is one of the countries that have the largest growth after China and India in the use of mobile phones. eMarkerter published that the number of mobile phone users in Indonesia increased by 37.1% from 2016 to 2019 and in 2019 it reached 92 million users. This study aims to develop a mobile phone recommendation system with a semantic web approach using the Simple Additive Weighting Method (SAW). The prototype system available online at http://mobile.oss.web.id that has 3 main features, namely searching, browsing, and recommendation features. The process of searching, browsing, and recommending the system using information that has been stored in Ontology. Meanwhile, the recommendation mechanism uses the SAW method as a method of calculating the weight of each cellphone and the weight of the criteria. Evaluation of functional requirements system using Black-Box testing approach, while evaluation of non-functional requirement systems using Technology Acceptance Model (TAM) approach by involving 32 respondents. The final result of the evaluation shows that the system functionality is running well as expected. Moreover, the evaluation of the non-functionality of the system showed that on average the respondents involved in the study agreed that the system developed was useful and easy to use